Marginalisasi dan Mekanisme Survival Komunitas di Kawasan Wisata Kenjeran Park Surabaya - Chaerunissa, Cynthia Amanda (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This research aims to explain the phenomenon of marginalization and the survival mechanism of the community in the middle of the urban tourism environment and its impact on social disorganization, limited access to basic rights, and a decrease in the quality of life of the community. The case study was conducted on the community in the Kenjeran Park tourism area in Surabaya. The marginalization experienced by the Kenjeran Park tourism community faces various problems, such as weak social control, environmental degradation, and loss of support for the development of local economic sustainability. This is because this tourist attraction, which was once crowded, is now facing the challenge of a lack of tourists, weak tourism attraction, and many tourism facilities that are stalled and not maintained. On the other hand, this environment is still inhabited and becomes the economic activity of the community, both fishermen, residents and street vendors who sell every day. This study was conducted using qualitative methods and a phenomenological approach. The results showed that the community experienced social disorganization characterized by poor social, cultural, and economic environment, weak social control, vulnerability to lawless activities, and a subsistence lifestyle. Marginalization in this case occurs due to the stagnation of tourism development and the lack of socio-economic structure support to build the quality of life of the community in the Kenjeran Park tourism area. This research is expected to contribute to identifying tourism development challenges and public policy recommendations to overcome community marginalization in urban tourism areas.